POTENSI DAN TANTANGAN PENGOMPOSAN KOMUNITAS DI RUMAH SUSUN SEWA MAKASSAR - Anggraini, Nani; Akrim, Djusdil; Muis, Ramdiana; Al Fariz, Reza Dharma; Tawakkal, Irfan; Rachman, Indriyani; Matsumoto, Toru (Program Studi Teknik Lingkungan Universitas Bosowa, 2025)
This study investigates the implementation of community-based composting technology in low-cost rental apartments (Rusunawa) in Makassar City, Indonesia, as a solution for organic waste management and to enhance environmental awareness. Rusunawa, characterized by its vertical structure and tenant-based system, often faces waste management challenges due to limited space and varying levels of environmental awareness among residents. The study aims to apply composting technology through a community development strategy to address organic waste issues using accessible and affordable methods. A mixed-methods approach was employed, integrating quantitative analysis of compost quality with qualitative assessment of community responses across several stages of outreach: general counseling, floor-by-floor engagement, communal garden cultivation, neighbor-to-neighbor outreach, and media promotion. The results show that household waste from Rusunawa residents can be converted into compost with phosphorus (P) and potassium (K) levels exceeding the Indonesian National Standard (SNI), although nitrogen (N) and carbon (C) levels require improvement. Following the outreach process, more than 50% of residents demonstrated increased environmental awareness and actively participated in composting activities, with media-based and neighbor-to-neighbor outreach proving the most effective. To improve compost quality, extended composting time and nutrient supplementation are recommended. The study advocates for the establishment of community-based organizations to ensure the long-term sustainability and effective management of composting initiatives in Rusunawa.